Perceived social support and prosocial behavior in medical students: Mediating effect of empathy and moderating role of moral identity - Yiping Wang; Huiying Zhang; Zhiqing Hu; Yuhao Ma; Yanjun Sun; Juhong Zhang; Yuan He (Acta Psychologica)
Background: Prosocial behavior is essential for effective patient communication and building a positive doctor-patient relationship in medical students. Research on the factors influencing prosocial behavior in medical students is limited. This research aims to examine how perceived social support influences prosocial behavior among medical students, focusing on the mediating role of empathy and the moderating role of moral identity. Methods: This cross-sectional study included 2425 medical students from central and southern Jiangsu province. Participants were assessed using the Prosocial Behavior Scale, Interpersonal Response Index Scale, Moral Identity Scale, and Perceived Social Support Scale, with data collected through via an online questionnaire. SPSS PROCESS macro model 4.1 was used to examine the mediating effect and the moderating effect. Results: Perceived social support showed a significant positive correlation with prosocial behavior among medical students. The indirect effects of perceived social support on prosocial behavior through perspective taking (βindirect = 0.11, 95% Boot CI [0.09, 0.13]) and empathic concern (βindirect = 0.08, 95% Boot CI [0.06, 0.10]) confirmed the mediating roles of these variables, accounting for 32.05% and 23.82% of the total effect, respectively. However, personal distress did not mediate this relationship (βindirect = −0.004, 95% Boot CI [−0.01, 0.005]). Moral identity significantly moderated the effect of perceived social support on perspective taking (β = 0.05, p < 0.01) and the relationship between perspective taking and prosocial behavior (β = 0.12, p < 0.001). Additionally, moral identity also moderated the relationships between perceived social support and empathic concern (β = −0.05, p < 0.01) and between empathic concern and prosocial behavior (β = 0.08, p < 0.001). While the interaction between perceived social support and moral identity predicted personal distress (β = 0.04, p < 0.05), moral identity did not moderate the relationship between personal distress and prosocial behavior (β = 0.03, p = 0.12). Conclusion: This study underscores the link between perceived social support and prosocial behavior, highlighting the significant roles of perspective taking, empathic concern, and moral identity in this relationship. These findings underscore the potential of cultivating these psychological mechanisms to foster caring and prosocial behaviors among medical students, providing important references for future educational interventions and policy formulation.